Risk Factors of Sexually Transmitted Infections among Women of Child-Bearing Age in IDP camps in Abuja - Judith I Ukwajiunor; Okwuoma C Abanobi; Chikere Ifeanyi C Ebirim; Sally NO Ibe; Christain C Nwachukwu (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Background: Sexually Transmitted Infections (STIs) are a major public health concern which is responsible for acute illness, infertility, long-term disability and death globally. The adverse effect is however profound in developing countries and among women when left untreated. In Nigeria, the Boko haram insurgence and other conflicts has given rise to internally displaced persons. The increased reports of STIs among internally displaced persons which women and children make up the largest population and the dearth of literature on epidemiological studies on STIs among internally displaced persons initiated the need for the study.  Aim: This study seeks to determine the risk factors of Sexually Transmitted Infections (STIs) among internally displaced women of child bearing age in Internally Displaced Persons Camps in Abuja.  Methodology: A community based retrospective case-control study design was used. Each consenting participant was screened to detect the presence of antibodies for Hepatitis B, C, HIV, and Syphilis using Rapid Diagnostic Tests. A self-administered structured questionnaire was used to assess risk factors among study participants after being validated and its reliability tested. Multistage sampling technique was used to select the study participants (n=362) and Cases and Controls were selected using set criteria.  Results: Data was entered and analysed using SPSS version 21. Chi- square was used to determine the association between variables and STI morbidity within the period of 6months and above prior to the study. Variables found to be significant in the analysis were entered into a multivariate logistic regression model to estimate the strength of the associations between these variables and STI morbidity. P-value<0.05 was considered statistically significant. With respects to Influence of socio-demographic characteristics as a risk-factor of STI there was significant association between marital status and STI morbidity. (X2=8.445, P=0.004). Sexual behaviours which were significantly associated as risk-factors of STIs were number of sexual partners (X2=4.032, P=0.045), use of sexual performance enhancers (X2=12.302, P=0.001). Furthermore, getting a reward for sex a variable of gender-based violence had a very significant association with STIs morbidity (X2=7.086, P=0.008). IDP mobility as a risk-factor for STI revealed that the nature of relationships study participants had outside the IDP camp was significantly associated with STIs (X2=5.710, P=0.017). The adjusted logistic regression model showed that the likelihood of STI morbidity was 1.8 times more among single respondents when compared to married respondents (OR=1.8). Respondents with no sexual partners were 1.5 times more likely to get an STI when compared with those who had sexual partners (OR=1.5). Furthermore, respondents who used sexual performance enhancers were 2.9 times more likely to have an STI when compared with those who used no form of sexual performance enhancer (OR=2.923, P-value=0.001).  Conclusion: This study found that risk factors for STIs which exists among internally displaced women of child bearing age in IDP camps in Abuja were; marital status, having a sexual partner, getting a reward for sex and having sexual relationships outside the IDP camp. However, the logistic regression model revealed that the use of sexual performance enhancers (OR=2.923 P=0.001 95% CI [1.597-5.348]) was the most significant risk factor of STIs among the study group. Thus, there is need for more comprehensive community based STI studies alongside implementation of risk targeted Public health intervention.